Regulation of SREBP Processing and Membrane Lipid Production by Phospholipids in Drosophila. - Dobrosotskaya, I.Y.; Seegmiller, A.C.; Brown, M.S.; Goldstein, J.L.; Rawson, R.B. (Science, 2002)
Animal cells exert exquisite control over the physical and chemical properties of their membranes, but the mechanisms are obscure. We show that phosphatidylethanolamine, the major phospholipid in Drosophila, controls the release of sterol regulatory element-binding protein (SREBP) from Drosophila cell membranes, exerting feedback control on the synthesis of fatty acids and phospholipids. The finding that SREBP processing is controlled by different lipids in mammals and flies (sterols and phosphatidylethanolamine, respectively) suggests that an essential function of SREBP is to monitor cell membrane composition and to adjust lipid synthesis accordingly.